2008
DOI: 10.2500/aap.2008.29.3126
|View full text |Cite
|
Sign up to set email alerts
|

Fluticasone furoate nasal spray: Effective monotherapy for symptoms of perennial allergic rhinitis in adults/adolescents

Abstract: Intranasal corticosteroids are widely prescribed for the treatment of perennial allergic rhinitis (PAR). The purpose of this study was to evaluate the efficacy and tolerability of intranasal fluticasone furoate, a novel enhanced-affinity glucocorticoid, in patients > or =12 years of age with PAR in a global, randomized, double-blind, placebo-controlled, 6-week study. Patients (n = 302) received fluticasone furoate nasal spray (FFNS) 110 microg or vehicle placebo once daily (q.d.). The primary efficacy measure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
40
3
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(48 citation statements)
references
References 26 publications
3
40
3
2
Order By: Relevance
“…Fluticasone furoate was associated with significant improvement compared with placebo in daily reflective eye redness score (P=0.01), but not in morning predose instantaneous eye redness score (P=0.076) [88].…”
Section: Seasonal Versus Perennial Allergymentioning
confidence: 99%
“…Fluticasone furoate was associated with significant improvement compared with placebo in daily reflective eye redness score (P=0.01), but not in morning predose instantaneous eye redness score (P=0.076) [88].…”
Section: Seasonal Versus Perennial Allergymentioning
confidence: 99%
“…Several studies have shown that the effects of mometasone, fluticasone and ciclesonide commence within a day of starting therapy (93). Intranasal corticosteroids probably also improve coexisting asthma (94-96) (A), and fluticasone furoate and mometasone may be effective for conjunctivitis (77,82,97) …”
Section: Intranasal Corticosteroidsmentioning
confidence: 99%
“…Newer, once-daily products (e.g. fluticasone propionate (98), mometasone (99)(100)(101), fluticasone furoate nasal spray (82)) are preferred as these have been shown, unlike beclomethasone, not impair growth velocity albeit only after a year of therapy (102, 103) (A). This is probably due to the much lower systemic bioavailability of the newer products (Fig.…”
Section: (B)mentioning
confidence: 99%
“…Individuals with both nasal and ocular symptoms may benefit from INSs treatment. Indeed, recent clinical trial evidence in adults showed that INSs provided relief from the ocular symptoms of SAR/SAC [20,21,84,85,86,87]. However, few INSs have demonstrated this effect consistently in well-controlled clinical studies.…”
Section: Discussionmentioning
confidence: 99%